Style and Stylistics in Literary Research: An Analysis Using the Examples of Goran and Dylan - Ali, Aram Omer; Wali, Awat Hassan; Hamafaraj, Dilan Salam; Abdulla, Kanyaw Bakr; Ali, Srwa Tahir; Abdalla, Shabaz (Journal of Linguistics and Social Sciences, 2024)
Stylistics, originally confined to literary criticism, evolved into an independent discipline with the expansion of linguistics. Beyond literature, style extends to the distinctive markers of individuals in public life, encompassing appearance, behavior, and content. Societies exhibit diverse cultural patterns and interpersonal dynamics. This paper delves into the exploration of stylistics, focusing on its manifestation in literary articles where writers convey emotions and thoughts, influenced by various principles. The study introduces style concepts, terminology, and methodologies, examining their impact on writers, texts, and readers. It analyzes style from the author's perspective, considering language choice, rhetorical devices, and mental state. Practical examples from selected poetic texts, including works by Goran and Dylan, illustrate literary style within this comprehensive exploration.